2009
DOI: 10.1177/1440783309103346
|View full text |Cite
|
Sign up to set email alerts
|

Bauman, strangerhood and attitudes towards immigrants among the Australian population

Abstract: Through an investigation of the idea of the stranger, this article seeks to blend theory with empirical research. It does this in three ways. First, it engages with a social theory of the stranger articulated in the work of Zygmunt Bauman. Second, it examines data from the Australian Election Study surveys between 1996 and 2007 in order to explore attitudinal changes towards groups of immigrants. The findings from this survey suggests that attitudes towards immigrants in general have fluctuated in Australia, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…296Á8) findings further tended to support the need for greater social class differentiation in any assessment of social divides. Pietsch and Marotta (2009) saw implicitly that this suggested a need for greater social class differentiation as linked to variations in concerns about job security and housing affordability among low-middle (working)-class groups, and more 440 J. Forrest & K. Dunn generally because of negative images increasingly being created about some ethnic immigrant groups.…”
Section: Class-based Differentiationmentioning
confidence: 96%
See 1 more Smart Citation
“…296Á8) findings further tended to support the need for greater social class differentiation in any assessment of social divides. Pietsch and Marotta (2009) saw implicitly that this suggested a need for greater social class differentiation as linked to variations in concerns about job security and housing affordability among low-middle (working)-class groups, and more 440 J. Forrest & K. Dunn generally because of negative images increasingly being created about some ethnic immigrant groups.…”
Section: Class-based Differentiationmentioning
confidence: 96%
“…Results for Brisbane highlighted the importance of recognising multiple constructions of attitudes towards immigrant groups from culturally different backgrounds. At a national level, Pietsch and Marotta (2009) have shown that tolerance of immigrants among the population generally depends on the recent history of attitude formation towards different groups as well as the cultural backgrounds of the immigrants themselves. Thus (Pietsch & Marotta 2009, pp.…”
Section: Analysis Stage Ii: Attitudes To Diversitymentioning
confidence: 99%
“…Louis and associates (2007) have further suggested intergroup processes related to social identity can lead to the endorsement of exclusionary behaviours. Taking another perspective, Pietsch and Marotta (2009) have drawn on the classic sociological concept of 'the stranger' to explain exclusionary beliefs. Studies such as these have all provided important theoretical insight into why Australians might exhibit exclusionary attitudes.…”
Section: The Attitudes Of Australians Towards Asylum Seekers and 'Boamentioning
confidence: 99%
“…Australia is a nation made up of Aboriginal Australians and a myriad of immigrants, some of the earliest of whom trace their ancestry to Britain (for a brief history of Australian immigration and policies post WWII, see Poynting and Mason 2007 ). While Australians’ attitudes toward immigrants have varied over the years, Pietsch and Marotta ( 2009 ) note certain patterns in these attitudes. For example, Australians have been generally positive toward the idea of skilled migrants, but prefer European migrants to Asian or Middle Eastern migrants; this preference was further aggravated by the events of 9/11.…”
Section: Cultural Diversity In Australiamentioning
confidence: 99%